2005
DOI: 10.1002/ccd.20338
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic aneurysm of left anterior descending artery after sirolimus‐eluting stent implantation: A case report

Abstract: We report a case of mycotic aneurysms due to Staphylococcus aureus infection in the left anterior descending coronary artery in a 56-year-old male after implantation of a sirolimus-eluting stent. This is an unreported complication of a drug-eluting stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…There has been no recurrence of fever or angina in the past 16 months. Table 1 (5,6,(10)(11)(12)(13)(14)(15)(16)). Bacterial cultures of blood in the present case repeatedly grew S. aureus (Fig.…”
Section: N T E R I O R O B L I Q U E ( L Ao) V I E W) : T H E R I G Hmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been no recurrence of fever or angina in the past 16 months. Table 1 (5,6,(10)(11)(12)(13)(14)(15)(16)). Bacterial cultures of blood in the present case repeatedly grew S. aureus (Fig.…”
Section: N T E R I O R O B L I Q U E ( L Ao) V I E W) : T H E R I G Hmentioning
confidence: 99%
“…Recently, coronary artery aneurysm formation is considered as one of complications after the use of sirolimus-eluting stent (SES), which markedly reduces the restenosis rate after coronary angioplasty (3,4). (5,6). Furtermore, the incidence of infected aneurismal fistula formation after stenting SES has not been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Potential causes for drugeluting stent infections include impairment of local immunosuppression and endothelialization caused by the paclitaxel or sirolimus released from the stent and/or bacteremia at the time of catheterization. [1][2][3][4] In fact, Ramsdale et al reported that up to 17.7% of patients who underwent complex percutaneous coronary interventions had detectable bacteremia. 5 Further investigation is warranted to determine whether drugeluting stents have a higher propensity for contamination versus bare-metal stents and whether prophylactic antibiotics should be administered for drug-eluting coronary stent implementation, particularly in complicated percutaneous coronary interventions.…”
mentioning
confidence: 99%
“…[1][2][3][4] In all cases S. aureus bacteremia was responsible for causing mycotic stent complications. Although mycotic aneurysms, pseudoaneurysms, and abscesses have been previously reported in both bare-metal and drug-eluting stent infections, this is the first reported case of an infected coronary stent that developed an intracardiac fistula.…”
mentioning
confidence: 99%
“…Therapy with intravenous antibiotics was chosen, however, considering that foreign body infections are extremely resistant to antibiotics, surgical debridement and/or stent removal could be necessary 5 . Our cases were managed with endovenous therapy, reaching a survival of 50%.…”
Section: Discussionmentioning
confidence: 99%